The improvement of strength performance during an Australian football pre-season. - Garrett, J. M.; McKeown, I.; Rogers, D. K. (Journal of Australian Strength and Conditioning, 2016)
The present study examined the changes in strength performance during an 11 week pre-season period in elite Australian football (AF). The aim was to describe strength performance changes during a heavy period of training where competing demands of conditioning and strength were trained in a relatively high volume. Fifteen professional AF players (mean ± SD: age 25.7 ± 2.8 years; height 187.7 ± 5.9 cm; body mass 86.2 ± 5.8 kg) from one AFL club, completed periodised strength, conditioning and skills training throughout an 11 week period of pre-season. Descriptive statistics (mean and SD) were calculated for all variables. Effect Size (ES) was calculated, using Cohen`s d statistic. 90% Confidence Interval (CI) were also calculated. Pearson`s correlations coefficient was calculated between an isometric mid-thigh pulls (Newton per kilogram (N/kg)), weekly conditioning load (total weekly distance (kilometres)) and strength volume (repetitions). An average of 35 km and 1427 repetitions a week was covered over this period. A small increase in strength was shown (5 ± 0.78 N/kg), resulting in a small change (13 ± 0.05% increase, ES 0.69 ± 0.29) across the pre-season period. A very large negative correlation (r = -0.82) was shown between N/kg and weekly conditioning load, presenting the possible presence of an interference effect over this period. The results of this study demonstrate the ability to increase maximum strength, during a period of heavy training where competing demands of conditioning and strength were trained in relatively high volume and in the presence of an interference effect.